Analysis of coal wettability by inverse gas chromatography and its guidance for coal flotation. (15th September 2018) - Niu, Chenkai; Xia, Wencheng; Peng, Yaoli
Highlights: IGC was used to characterize wettability and hydrophobicity of fine coal. A good correlation between flotation recovery and surface energy was found. IGC is a potential method for predicting the flotation recovery of fine coal. A higher hydrophilicity index of coal leads to a lower flotation recovery. Abstract: In coal flotation, the hydrophobicity of fine coal is a crucial factor that affects coal flotation recovery and performance. How to accurately characterize the surface hydrophobicity of coal becomes a research hot spot in coal science. This paper used a novel characterization technology, namely inverse gas chromatography (IGC) to characterize the wettability and hydrophobicity of fine coal particles by analyzing their surface energy. Five coals with different coal ranks were used as coal samples in this investigation, and the flotation results of five coal samples were obtained under the same flotation conditions. Throughout this paper, a good correlation between flotation recovery and surface energy was found and the hydrophilicity index of coal was calculated using the ratio of the specific component of surface energy to the total surface energy. A higher hydrophilicity index of coal leads to a lower flotation recovery. The flotation recovery is not governed by the coal rank but is determined by the surface energy of coal particles, i.e. the hydrophilicity index and the work of adhesion. The IGC is demonstrated to be a potential method for predicting the flotation recovery of fine coal in the coal preparation industry.